Investigation of Groundwater Quality using Vertical Electrical Sounding and Dar Zarrouk Parameter in Leihitu, Maluku, Indonesia - Samsul Bahri; Aditya Ramadhan; Zulfiah (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
The goal of this research is to obtain information related to aquifer quality, including aquifer protection capacity, transmissivity, and aquifer thickness based on vertical electrical sounding (VES) data and Dar-Zarrouk parameter analysis. The research area is located in Leihitu District, Ambon with 8 measurement points. The Leihitu region is included in the geological map of the Ambon sheet, Maluku, which consists of Late Pliocene - Holocene lithology, specifically Ambon volcanic rocks, reef limestones, and alluvial deposits. The rock resistivity measurements and layer thickness information were obtained using the VES method and analyzed with IP2WIN software. Based on VES data, aquifer properties were identified using Dar-Zarrouk parameters. That parameter consisted of longitudinal conductance, transfer resistance, longitudinal resistivity, and transfer resistivity. Longitudinal unit conductance is applied to evaluate the protective capacity class of the aquifer, the transfer resistance is beneficial for analyzing rock type and aquifer transmissivity. Based on the Dark-Zarrouk parameters, the longitudinal conductance (S) ranged from 0.0278 to 5.1213 mho and was classified as moderate to good protective capacity. The high S value results from a thick layer of clay at the observation point. This area also has a high enough transverse resistance (T) and then if related to aquifer transmissivity, this area is classified as a good transmissivity aquifer, especially at VES 2, VES 5, VES 6, VES 7, and VES 8. If correlated to rock formations, areas with limestone and volcanic rocks have better transmissivity than areas with alluvial deposits.